A panel of microsatellite markers to discriminate and study interactions between Haemonchus contortus and Haemonchus placei - Santos, Michelle C. [UNESP] (2017)
Haemonchus contortus and Haemonchus placei are two closely related economically important parasites of ruminants. Their close morphological similarity, common occurrence as co-infections and ability to hybridize makes definitive diagnosis and epidemiological studies in field populations challenging. In this paper, we describe the development of a panel of microsatellite markers that can be used to discriminate and study the genetics of these two parasite species in co-infections and mixed field populations. We have identified two additional microsatellites (Hp52 and Hp53), in addition to three previously reported microsatellites (Hcms3561, Hcms53265 and Hcms36) that have a discrete set of alleles between the two species. Multilocus genotyping of worms with this 5 marker panel from 3 geographically diverse H. placei isolates and 4 geographically diverse H. contortus populations allows unambiguous species assignment of individual worms. This panel of markers should provide a valuable resource in studying the biology and epidemiology of these important ruminant parasite species in the field.